A definite bite by the Ornamental Snake (Denisonia maculata) causing mild envenoming. (15th March 2016) - Isbister, Geoffrey K.; Gault, Alan; Tasoulis, Theo; O'Leary, Margaret A.
Abstract: Context : Many bites from mildly venomous elapids occur but identification or presence of systemic envenoming is rarely confirmed.Objective : To confirm systemic envenoming and binding of venom components to a commercial antivenom in a definite bite by the Ornamental Snake ( Denisonia maculata ) using enzyme immunoassays.Case : A 9-year old boy was bitten by an identified Ornamental Snake. He developed nausea, vomiting, local pain, and swelling. He had a leucocytosis (white cell count, 20.8 × 10 9 /L), an elevated international normalised ratio (INR) of 1.6, but otherwise normal blood tests including D-Dimer and activated partial thromboplastin time. He was treated with Australian Black Snake antivenom because the commercial venom detection kit was positive for Black snake. He was admitted for 36 h with continuing local pain and swelling requiring parenteral analgesia.Materials and methods : Blood samples were collected with informed consent for measurement of venom and antivenom concentrations. Venom-specific enzyme immunoassays were developed using the closely related D. devisi venom with Rabbit anti- Notechis (Tiger Snake) and anti- Tropidechis (Rough-scaled Snake) IgG antibodies to detect venom in serum. Standard curves for measured venom versus actual venom concentrations were made to interpolate Denisonia venom concentrations. In vitro procoagulant and anticoagulant activity of venom was assayed.Results : Denisonia venom was detected in the pre-antivenom sample as 9.6 ng/mL D. devisi venom. No antigenic venom components were detected in post-antivenom samples and there were high antivenom concentrations. D. devisi venom had mild in vitro procoagulant activity with a minimum concentration required to clot after 5 min of 2.5–5 μg/mL and even weaker anticoagulant activity.Conclusions : Denisonia bites appear to cause local effects and possibly mild systemic envenoming (with only non-specific systemic symptoms and leucocytosis), confirmed by detection of antigenic venom components in blood. A significant coagulopathy does not appear to occur.